Probing dark matter with star clusters: a dark matter core in the ultra-faint dwarf Eridanus II. Issue 3 (19th February 2018) - Contenta, Filippo; Balbinot, Eduardo; Petts, James A; Read, Justin I; Gieles, Mark; Collins, Michelle L M; Peñarrubia, Jorge; Delorme, Maxime; Gualandris, Alessia
Abstract: We present a new technique to probe the central dark matter (DM) density profile of galaxies that harnesses both the survival and observed properties of star clusters. As a first application, we apply our method to the 'ultra-faint' dwarf Eridanus II (Eri II) that has a lone star cluster ∼45 pc from its centre. Using a grid of collisional N -body simulations, incorporating the effects of stellar evolution, external tides and dynamical friction, we show that a DM core for Eri II naturally reproduces the size and the projected position of its star cluster. By contrast, a dense cusped galaxy requires the cluster to lie implausibly far from the centre of Eri II (>1 kpc), with a high inclination orbit that must be observed at a particular orbital phase. Our results, therefore, favour a DM core. This implies that either a cold DM cusp was 'heated up' at the centre of Eri II by bursty star formation or we are seeing an evidence for physics beyond cold DM.